Analysis of biomass yield and chemical composition of elephant grass at different growth stages (Research, Society and Development, 2025)
Planting conditions and harvest timing significantly influence the morphological composition and quality of elephant grass. The objective of this study was to evaluate the dry matter production and compositional changes of elephant grass in terms of ash, extractives, protein, lignin, cellulose, and hemicellulose contents at different growth stages (60 days, 90 days, 120 days, and 60 days regrowth) to recommend ideal harvest periods for specific applications. During the experimental period, favorable climatic conditions prevailed, with temperatures ranging from 17.3 °C to 32.2 °C and cumulative precipitation totaling 1,178 mm. Ash content decreased from 7.2% at 60 days to 4.8% at 120 days, while lignin content increased significantly from 16.9% to 32.7%, reflecting structural changes with plant maturity. Based on these findings, shorter harvest intervals (e.g., 60 days or 60-day regrowth) are recommended for energy generation and forage production due to the lower ash content and higher biodegradability. In contrast, longer growth periods (e.g., 90-120 days) are preferable for applications requiring higher cellulose, hemicellulose, and lignin fractions in lignocellulosic biorefineries.